Monetary policy, investment and firm heterogeneity - Elena Durante; Annalisa Ferrando; Philip Vermeulen (European Central Bank (ECB), 2020)
This paper provides new evidence on the channels of monetary policy transmission combining 9 million observations on firm level investment and high-frequency identified monetary policy shocks. We show that the reaction of firms' investment to a monetary policy shock is heterogeneous along dimensions that correspond to the two main channels of monetary policy transmission. First, we show that young firms are more sensitive to monetary policy shocks, supporting the existence of a credit channel of monetary policy. Second, we document large cross-sectional heterogeneity related to the industry the firm operates in. We find that firms producing durable goods react more than others, which is consistent with traditional interest rate channel effects of monetary policy. Third, we find that the effect of monetary policy shocks is longer lived for firms that are durable goods producers than for young firms indicating that demand effects last longer than credit effects.
Keywords: E22; E52; 330; monetary policy transmission; monetary policy shocks; investment